Phenology of southward migration of shorebirds in the East Asian-Australasian Flyway and inferences about stop-over strategies. (1st June 2016) - Choi, Chi-Yeung; Rogers, Ken G.; Gan, Xiaojing; Clemens, Roberts; Bai, Qing-Quan; Lilleyman, Amanda; Lindseyf, Ann; Milton, David A.; Straw, Phil; Yu, Yat-tung; Battley, Phil F.; Fuller, Richard A.; et al.
Abstract: The southward migration strategies of shorebirds remain poorly understood in the East Asian-Australasian Flyway, yet understanding such strategies is critical to shorebird conservation. We estimate passage dates of 28 species of shorebird from count data at 15 sites to infer their migration strategies, using Thompson's modelling approach. Our estimates of passage dates were consistent with available tracking data, giving us confidence that the modelled estimates were accurate. For large-bodied shorebirds, modelled departure dates from the northern Yellow Sea were similar to arrival dates throughout Australia, and their arrival dates in different regions in Australia were also similar, suggesting they flew directly from Asian staging areas to Australian non-breeding areas, or stopped only very briefly on the way. In contrast, small-bodied species apparently made multiple stops, especially in northern Australia, during their migration to their final non-breeding destinations. These differing patterns suggest that larger species in this Flyway depend on a small number of staging sites, whereas smaller species migrate in shorter steps and require additional staging sites between the northern Yellow Sea and Australasia. It is likely that some of these sites have not as yet been discovered, and that conservation of small shorebird species requires a more complete accounting of unknown and understudied staging sites.